Measuring dynamic emotional experiences in response to media stimuli - Winkler, Julia R.; Appel, Markus (Frontiers in Psychology, 2024)
Communication research has long recognized the dynamic nature of most media stimuli and the corresponding dynamic emotional processing implied on the side of the audience. Capturing and analyzing these emotional dynamics during media reception is imperative for advancing our understanding of media processing and effects, but is not common practice in most communication research. This article highlights several methodological approaches to measuring the physiological, behavioral, and experiential components of emotions during media exposure: Electrodermal activity, automated facial expression analysis, continuous response measurement, and self-probed emotional retrospections. We discuss these methods in terms of what they measure, their practical application to different research contexts, and aspects of data-analysis. We further highlight ways to adapt and apply these methods to advance research on hot topics in communication science, psychology, and related fields and provide recommendations for scholars who wish to integrate continuous measures of emotional responses into their research.